Velocity-free friction compensation for motion systems with actuator constraint. (1st February 2021) - Su, Yuxin; Zheng, Chunhong; Mercorelli, Paolo
Highlights: Propose a simple model-free saturated output feedback robust PD control for friction motion systems. Prove global asymptotic positioning stability by Lyapunov's direct method. Features are it is model–free with position measurements only and avoidance of actuator saturation. Demonstrate the improved performance through numerical simulations and real-time experiments. Abstract: This paper concerns on the output feedback problem of fast and precise positioning for uncertain motion systems subject to friction and actuator constraint by position measurement only. A simple model-independent saturated robust output feedback nonlinear proportional-derivative (PD) control is proposed by adding relay action driven by position error. Lyapunov's direct method is employed to prove global asymptotic positioning stability. The appealing advantages of the proposed approach are that it is fairly easy to construct with simple and intuitive structure and without reference to modeling parameter and velocity measurement and has the ability to ensure that the actuator constraint is not violated. This is accomplished by selecting control gains a priori. Numerical simulations and real-time experimental validations demonstrate that the proposed approach provides an easy-going model-free solution for high performance positioning of uncertain motion systems subject to unknown friction and actuator constraint with position measurement only.